Effect of interleukin-1 antagonist on growth of children with colchicine resistant or intolerant FMF - Shiran Pinchevski-Kadir; Maya Gerstein; Oren Pleniceanu; Yonatan Yacobi; Asaf Vivante; Ortal Erez Granat; Shiri Spielman; Rotem Semo Oz; Irit Tirosh (BMC, 2023)
Abstract Introduction Familial Mediterranean Fever (FMF) is the most common monogentic autoinflammatory disease. FMF results from mutations in MEFV, which lead to a pro-inflammatory state and increased production of Interleukin 1 beta subunit (IL-1b) by myeloid cells. Despite the overall positive results obtained with anti-IL-1 agents in FMF patients, little is known about the long-term growth impact of these drugs in the pediatric population. Objectives To assess the long-term body weight and height trajectories in children with FMF treated with anti-IL-1 agents. Methods We conducted a retrospective analysis of 646 pediatric FMF patients followed in our center, of whom 22 were treated with either anakinra (36.3%) and/or canakinumab (90.9%). Patients were assessed for demographic, clinical and genetic characteristics and were followed for a mean of 3.05 ± 1.75 years. Data of height and weight percentiles were recorded before and after treatment. Results The most common indication for IL-1 blockers treatment was colchicine resistance (66.6%). Ninety percent of those patients had a moderate or severe disease according to the Pras score and had higher proportion of M694V homozygosity compared with patients who did not require anti IL-1 agents (95.2% vs. 30.5%, p < 0.001). Overall, anakinra and canakinumab resulted in a complete response in 80% of patients and exhibited low rates of adverse effects. We found a significant increase in height and body weight percentiles following treatment (19.6 ± 16% vs. 30.8 ± 23%, p = 0.007, and 29.5 ± 30% vs. 39.1 ± 36%, p = 0.043, respectively). Conclusion Treatment with anti-IL-1 agents in children with FMF is effective and safe and may potentiate long-term growth.